Упражнения по развитию письменной речи на начальном этапе обучения русскому языку (анализ учебников) - Smoła, Joanna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The article presents the analysis of students’ books and exercise books for teaching Russian on elementary level in Polish schools. The author tried to prove that teaching creative writing skills is probable at the beginner level. We found many exercises to teach and improve creative writing skills. Some of them were interesting and according to students’ expectations and interests.
Keywords: письменная речь; упражнения в письменной речи; начальный этап; психологические механизмы; учебник; тетрадь для упражнений; creative writing; writing exercises; elementary level; psychological mechanisms; students’ book; exercise book